PENGARUH IMPLEMENTASI E-PAYMENT DAN KUALITAS PRODUK TERHADAP KINERJA UMKM (STUDI KASUS PADA USAHA PRODUK HOBI ALAT PANCING) - Rizki Aji Subekti; Reza Widhar Pahlevi (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
This study aims to examine the effect of E-Payment Gateway on the performance of MSMEs in fishing shops in the Yogyakarta and Magelang areas. This study uses a quantitative research approach with multiple linear regression method. The variables used are E-payment Gateway, product Quality, MSMEs Performance. The type of data used in this research is primary data which is taken directly by distributing questionnaires, namely micro business actors who are engaged in selling fishing rods. The results of this study indicate that the use of the E-Payment Gateway can improve the performance of MSMEs in fishing shops.